Evaluation and utilization of a kinetic enzyme direct measuring photometer. Issue 7 (July 1975) - Wolf, P L
Abstract : We have recently utilized a prototype model of the Beckman Enzyme Activity Analyzer System-TR in our laboratory measuring various serum enzyme activities which include: alkaline phosphatase (ALP), E.C.3.1.3.1; creatine kinase (CK), E.C.2.7.3.2; hydroxybutyrate dehydrogenase (HBD), E.C.1.1.1.30; lactate dehydrogenase (LD), E.C.1.1.1.27; aspartate transaminase (AST), E.C.2.6.1.1; and alanine transaminase (ALT), E.C.2.6.1.2. Precision was found to be good. Sample activities could be measured as high as 1000 IU/1. The carryover studies fell within 2 SD of the means of the enzyme control studies. Coefficients of variation for ALP and CK were in the ranges of 0-40-2-14% and 0-52-4-30%, respectively. Correlation studies were done with GemSAEC and Gilford 300 N Spectrophotometer and the results were accurate, precise, and reproducible.